Cognitive and adaptive functioning after severe TBI in school-aged children. (July 2013) - Recla, Monica; Bardoni, Alessandra; Galbiati, Susanna; Pastore, Valentina; Dominici, Chiara; Tavano, Alessandro; Locatelli, Federica; Strazzer, Sandra
Abstract Objective: Persistent cognitive and behavioural deficits have been documented in children suffering severe TBI. The aim of the present study was to examine the cognitive and adaptive profile of children of school age with severe TBI. Methods: This study selected 118 patients and divided them into three groups according to the severity of their clinical-functional picture. All the patients received a functional assessment using the Wee-FIM. Subjects with reduced responsiveness were evaluated by LOCFAS. Last, the cognitive profile children with a better recovery were described with WISC-III and Leiter-R and their adaptive behaviour with VABS. Results: Group 1 (n = 77) showed a borderline cognitive level with a disharmonious profile between VIQ and PIQ, significant deficits in the Processing Speed and Perceptual Organization Indices, lastly specific adaptive behavioural deficits. Length of coma correlated with their cognitive and adaptive profile. Group 2 (n = 14) included subjects with severe language and/or motor disabilities presenting with a partial cognitive functioning level moderately impaired. Group 3 (n = 27) included patients with reduced responsiveness (LOCFAS ≤ 3). Conclusions: In the first 12 months following severe TBI, 22.9% children stayed in minimal responsiveness, 11.9% showed debilitating language and motor deficits and 65.2% showed a more favourable cognitive recovery and could be assessed by WISC-III.